Short term effects of dexamethasone on hyaluronidase activity and sperm characteristics in rams - Gür, S; Bozkurt, T; Türk, G (My University, 2005)
The aim of this study was to determine the effects of dexamethasone on sperm characteristics and hyaluronidase activity of serum and semen. In this investigation, 14 healthy Akkaraman rams, at the age of 2 years and weighing between 50–60 kg, were used. The rams were randomly divided into two groups. After the last administration of dexamethasone intramuscularly at a dose of 0.25 mg/kg, semen and blood samples were taken at different times. The results showed that the serum hyaluronidase activity was increased significantly (p < 0.001) in the treatment group when compared with the control group except for the 1st hour. There was a significant difference (p < 0.001, 0.01, 0.05) in the hyaluronidase activity of semen between the treatment group and the control group. Furthermore, there was a significant difference (p < 0.01) in sperm concentration between both groups at all the times except the 96th hour. There were statistically significant (p < 0.05) differences in semen volume between the treatment and control groups. There were also significant differences (p < 0.05) in sperm motility between the treatment and control groups except for the 72 and 96th hours. These findings indicate that dexamethasone increases hyaluronidase activity of serum and semen, but it decreases sperm concentration, semen volume and sperm motility in rams. Therefore the use of these drugs in breeding rams during breeding season is not suitable.
Koçlarda deksametazonun hyaluronidaz aktivitesi ve sperm özellikleri üzerine kısa süreli etkileri
Makale - Yabancı Dilde Makale
Keywords: Dexamethasone Hyaluronidase Serum Semen Ram